d(-)-Lactic Acid Production by Leuconostoc mesenteroides B512 Using Different Carbon and Nitrogen Sources - Coelho, Luciana Fontes [UNESP]; Bolner de Lima, Cristian J. [UNESP]; Bernardo, Marcela Piassi [UNESP]; Contiero, Jonas [UNESP] (Humana Press Inc, 2011)
Sugar concentration from sugarcane juice and yeast autolysate increased lactic acid production more than the other agro-industrial substrates tested. The concentrations of these two components were further optimized using the Plackett-Burman design and response surface method. A second-order polynomial regression model estimated that a maximal lactic acid production of 66.11 g/L would be obtained when the optimal values of sugar and yeast autolysate were 116.9 and 44.25 g/L, respectively. To validate the optimization of the medium composition, studies were carried out using the optimized conditions to confirm the result of the response surface analysis. After 48 h, lactic acid production using the shake-flask method was at 60.2 g/L.
Keywords: Response surface method; Medium optimization; D(-)-Lactic acid; Residues